2018
DOI: 10.1038/s41598-018-19743-x
|View full text |Cite
|
Sign up to set email alerts
|

Drylands soil bacterial community is affected by land use change and different irrigation practices in the Mezquital Valley, Mexico

Abstract: Dryland agriculture nourishes one third of global population, although crop irrigation is often mandatory. As freshwater sources are scarce, treated and untreated wastewater is increasingly used for irrigation. Here, we investigated how the transformation of semiarid shrubland into rainfed farming or irrigated agriculture with freshwater, dam-stored or untreated wastewater affects the total (DNA-based) and active (RNA-based) soil bacterial community composition, diversity, and functionality. To do this we coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 75 publications
2
34
0
2
Order By: Relevance
“…Differences in the explanatory power of environmental variables between rDNA and rRNA-based community compositions have been reported only in a few studies comparing outcomes from both metabarcoding templates (i.e., Barnard et al, 2013; Zhang et al, 2014; Lüneberg et al, 2018). Yet it seems important to understand which parameters are crucial for shaping the community composition.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in the explanatory power of environmental variables between rDNA and rRNA-based community compositions have been reported only in a few studies comparing outcomes from both metabarcoding templates (i.e., Barnard et al, 2013; Zhang et al, 2014; Lüneberg et al, 2018). Yet it seems important to understand which parameters are crucial for shaping the community composition.…”
Section: Discussionmentioning
confidence: 99%
“…The numeric results represent a fraction of the community that matched with the functional database, and indicate the community proportions containing each specific function. We filtered a total of 106 KEGGs (functional orthologs) within 30 metabolic pathways (Llorens-Marès et al, 2015), including five additional phosphorous cycle pathways (G-3-P transport, phosphate transport -high and low efficiency-, phosphonate transport, and phosphonate metabolism) (Vila-Costa et al, 2013), and four complex OM decomposition pathways (chitin, cellulose, hemicellulose, and lignin) (Lüneberg et al, 2018).…”
Section: Functional Predictionmentioning
confidence: 99%
“…However, this can obviously affect normal development of plants and functional properties of soils receiving this nonconventional water. Moreover, many studies have been assessed the effect of TWW reuse on soils, plants and soil organisms [50,51,52,53,54,55] and in most cases they found that those effluent modify the physicochemical properties of soils, and physiological properties of plants and other organisms.…”
Section: IVmentioning
confidence: 99%